Programação da produção de um estaleiro náutico - Oliveira, Vagner Andrade de (2011)
This work addresses the optimization of short term production planning in a nautical shipyard. The current competitiveness of this sector motivates the need for optimized use of manufacturing resources. An action in this direction is to employ computing systems that can improve the decision making of scheduling activities. It aims to meet the delivery due dates of products with rational use of productive resources. The used raw material is fiberglass, thus involving their manufacturing processes. And the models of products compete for the use of a limited number of resources (eg, workstations and lamination molds). The main objective is to minimize the idleness of the bottleneck workstation in the manufacturing of parts. A computational approach was developed based on Mixed Integer Linear Programming (MILP), where the original problem is decomposed into smaller problems that are easily solved. These smaller problems consist of a smaller cluster of products, which were named as campaigns. After the generation of possible campaigns, a mathematical model allows to define which campaigns should be produced to meet the demand of products. In literature, there are few researches driven to this sector. The results obtained for all the campaigns and for a varied production mix indicate that the proposed approach is able to successfully address this real problem.